The inﬂuence of probiotic fermentation on Catharanthus roseus functional properties - Moghadam, Somayeh Moradi; Meor Hussin, Anis Shobirin; Mustafa, Shuhaimi; Mirhosseini, Seyed Hamed; Abdul Manap, Mohd Yazid
In this study, investigation of the inﬂuence of probiotic fermentation on the functional properties of the C.roseusextract was carried out. Historically Catharanthus roseus also known as kemunting cina had been used for various treatments. The use of probiotics in fermented plants has become very popular in recent years for providing health beneﬁts in human beings. Lactobacillus acidophilus LA5 and Lactobacillus casei-01 were used alternately to ferment the C. roseus extract anaerobically at 37◦C for 9 days. Several parameters such as pH, viable probiotic cell counts, changes in car- bohydrates and organic acids as well as antioxidant activity of the fermented C. roseus extract was evaluated during the fermentation process. During the fermentation, Lactobacillus casei-01 produced the lower pH and the viable counts of Lactobacillus acidophilus LA5 and Lactobacillus casei-01 were 7.82±0.015log10 CFU/mL and 8.04±0.040log10 CFU/mL, respectively at the end of the fermentation. Both strains utilized glucose, fructose and sucrose during fermentation. The contents of organic compounds (citric, acetic, lactic) were signiﬁcantly (p<0.05) affected by the types of the microorganisms. The study found that the fermentation had a positive effect on the antioxidant activity of the samples.